2x - 3 = 2x - 52x = 2x - 22x - 2x = -20 =/= -2Zero is not equal to -2 so the answer is no solution.
2x - y = 2 2x - y = -2 This system is inconsistent -- that is, there is no solution. To help see why, let Z = 2x - y and notice Z can't be 2 and -2 at the same time.
x - 3y = -3: multiply by -2 giving -2x + 6y = 6, but -2x + 6y = 12 so we have a problem! Misprint?
y=2x-4 y=2x-5 y=1 1=2x-4 -2x = -5 x=2/5 the solution is (x,y) = (2/5,1)
Yes it is!
2x + 3 = 72x = 4x = 2
No because x = 2
It does if x=2. That's the solution of your equation.
The answer is (3.5)2 plus (4)2 equals 410.